South Africa and Africa. Issue 1 (March 2014) - Saunders, Chris
This article examines aspects of the complex relationship between South Africa and the rest of Africa from the presidency of Nelson Mandela through those of Thabo Mbeki and Jacob Zuma, showing how the relationship changed over time and exploring the influences that shaped South Africa's policy on and toward the continent—a policy that has largely been determined by the presidency rather than the Department of Foreign Affairs/International Relations and Co-operation. To understand the changing relationship between South Africa and the rest of the continent, it is necessary to consider, first, the history before 1994, then the dramatically altered situation that the transfer of power in South Africa brought about, Thabo Mbeki's interventionist approach to Africa in general, and Jacob Zuma's ambiguous involvement in continental affairs. The article concludes with some speculative thoughts on the role that South Africa may play on the continent in the future.